Reconstruction of Administrative Sanctions as the Primary Instrument for Medical Malpractice Law Enforcement in Indonesia - Yeni Vitrianingsih; Rahayu Mardikaningsih (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
The enactment of Law Number 17 of 2023 concerning Health has fundamentally transformed the enforcement of medical malpractice law in Indonesia by shifting its orientation from criminal punishment to administrative accountability. However, the law does not provide clear standards for determining proportional administrative sanctions, creating legal uncertainty for both patients and medical personnel. This study aims to reconstruct the framework of administrative sanctions as the primary mechanism (ultimum remedium) for resolving medical malpractice disputes while ensuring a balance between patient protection and legal certainty for healthcare professionals. This research employs a normative legal method using statutory and conceptual approaches to examine the legal framework governing administrative sanctions. The findings reveal that the existing regulatory framework remains predominantly bureaucratic and punitive, lacking clear proportionality criteria and restorative mechanisms. The study proposes a reconstructed model of administrative sanctions based on restorative justice principles and the principles of carefulness and proportionality within good governance. It further emphasizes strengthening the authority and independence of the Medical Personnel Discipline Honor Council as the principal institution responsible for adjudicating professional disciplinary violations. This reconstruction contributes to the development of a more balanced medical malpractice enforcement system by enhancing patient safety, preventing arbitrary administrative decisions, and providing greater legal certainty for medical professionals.